Acute Patellofemoral Dislocation: Controversial Decision-Making - Rund, Joseph M. (Curr Rev Musculoskelet Med, 2021)
PURPOSE OF REVIEW: The topic of acute patella dislocations is controversial. Discussions revolve around which individuals need early surgery, identification of risk factors, and rehabilitation protocol. The purpose of this review is to discuss the current recommendations for non-operative and/or operative management of first-time dislocators. RECENT FINDINGS: Recent studies have made it clear that not all patellar dislocations are the same, not all patients do well with conservative treatment, and risk stratification can identify individuals at high risk of recurrence who would benefit from early surgical intervention. Risk factors that have been identified include younger age, skeletally immature, contralateral instability, trochlear dysplasia, patella alta, increased tibial tubercle-trochlear groove distance, and increased patella tilt. The PAPI (Pediatric and Adolescent Patellar Instability) RCT study and JUPITER (Justifying Patellar Instability Treatment by Early Results) prospective cohort study have been carefully developed, are under way, and will provide further guidance. SUMMARY: In summary, the management of acute patellar dislocations is evolving. Surgery for patients with osteochondral loose bodies should include fixation as well as soft tissue stabilization. The standard of care for patients with an acute patellar dislocation without osteochondral loose bodies or fracture is non-operative treatment. However, imaging for all first-time dislocators is indicated to stratify risks and determine risk profile. If an individual is at high risk, soft tissue stabilization may be considered. Still, most patients will be treated non-operatively.